Selective gas phase hydrogenation of maleic anhydride over Ni-supported catalysts: Effect of support on the catalytic performance - Regenhardt, Silvina Andrea (2012)
The gas phase hydrogenation of maleic anhydride to obtain γ-butyrolactone was studied using Ni supported on SiO2, SiO2–Al2O3 and zeolite H-BEA as catalysts. The samples were prepared by incipient wetness impregnation and characterized by N2 adsorption at −196 °C (Sg), X-ray diffraction (XRD), temperature programmed reduction (TPR), temperature programmed desorption of NH3 (TPD-NH3) and chemisorption of H2. The reaction was carried out at 170 °C and 220 °C in a fixed bed reactor operating at atmospheric pressure. From the characterization results, it was determined that the degree of Ni2+–support interaction varies according to the following pattern: Ni/HBEA > Ni/SiO2–Al2O3 > Ni/SiO2. All catalysts were very active in the hydrogenation of maleic anhydride to succinic anhydride. However, hydrogenolytic activity and stability of nickel-based catalyst varies with the degree of interaction Ni2+–support. Ni/H-BEA, in which Ni2+–support interaction is the highest, was active in the hydrogenolysis of succinic anhydride to γ-butyrolactone but it was not stable. By contrast, Ni/SiO2–Al2O3 and Ni/SiO2, with medium or low degree of Ni2+–support interaction, were more stable than Ni/H-BEA. In addition, Ni/SiO2–Al2O3, with a medium degree of Ni2+–support interaction, was the most stable and selective to γ-butyrolactone, especially when the reaction was carried out at 220 °C.